2012
DOI: 10.7852/ijie.2012.25.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression and Enzyme Activity of Chymotrypsin-like Protease from Black Soldier Fly, Hermetia illucens (Diptera: Stratiomyidae)

Abstract: Chymotrypsin serine protease is one of the main digestive proteases in the midgut of and is involved in various essential processes. In a previous study, a gene encoding a chymotrypsin-like protease, Hi-SP1, was cloned from the larvae of Hermetia illucens and characterized. In this study, we produced the recombinant chymotrypsin-like protease Hi-SP1 in Escherichia coli cells. The molecular weight of the recombinant Hi-SP1 was estimated to be approximately 26 kDa by sodium dodecyl sulfate-polyacrylamide gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, economicallyimportant bioproducts such as protein hydrolysates (Firmansyah and Abduh, 2019), bioplastic (Barbi et al, 2019), and natural pigments (e.g., melanin and ommochromes) (Ushakova et al, 2019) could also be derived from BSF biomass. Studies have also explored BSF biomass as a potential source of industrially important enzymes (e.g., trypsin, chymotrypsin, ligninase, and cellulase) (Bonelli et al, 2019;Kim et al, 2011;Lee et al, 2014;Muller et al, 2017;Park et al, 2012) and antimicrobial peptides. The successful development of a BSF-based biorefinery, however, will require a large-scale production of BSF biomass, which in turn will require mechanization and automation of rearing, harvesting, and processing.…”
Section: Black Soldier Fly-based Biorefinerymentioning
confidence: 99%
“…Moreover, economicallyimportant bioproducts such as protein hydrolysates (Firmansyah and Abduh, 2019), bioplastic (Barbi et al, 2019), and natural pigments (e.g., melanin and ommochromes) (Ushakova et al, 2019) could also be derived from BSF biomass. Studies have also explored BSF biomass as a potential source of industrially important enzymes (e.g., trypsin, chymotrypsin, ligninase, and cellulase) (Bonelli et al, 2019;Kim et al, 2011;Lee et al, 2014;Muller et al, 2017;Park et al, 2012) and antimicrobial peptides. The successful development of a BSF-based biorefinery, however, will require a large-scale production of BSF biomass, which in turn will require mechanization and automation of rearing, harvesting, and processing.…”
Section: Black Soldier Fly-based Biorefinerymentioning
confidence: 99%
“…Since 1977 the concentration for erucic acid in food is not allowed to exceed 5% in Germany [33]. trypsin and chymotrypsin activity has been published [34,35]. In 2014, Lee et al furthermore heterologously expressed a novel cellulase gene from the gut microflora and characterized the resulting enzyme which shows 72% identity and 80% homology to the glycosyl hydrolase family 5 of Dysgonomonas mossii [36].…”
Section: Lipidsmentioning
confidence: 99%
“…Moreover, a qualitative and quantitative comparison of the digestive enzymatic activity from M. domestica and H. illucens larvae demonstrated that the latters possess more digestive enzymes with higher levels of activity ( Kim et al, 2011b ), a finding that supports the extraordinary digestive capability of H. illucens . Finally, two serine proteases were cloned and characterized ( Kim et al, 2011a ; Park et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%